(untitled) (Tạp chí Y học Cộng đồng, 2025)
Objective: To assess the current status and training needs related to continuing medical education (CME) among healthcare personnel at Nong Nghiep General Hospital. Research subjects and methods: A cross-sectional descriptive study was conducted involving 385 healthcare workers, comprising 85 physicians and 300 nurses currently employed at Nong Nghiep General Hospital. Data were collected using a structured questionnaire with three sections: demographic information, participation in CME activities during the 2023–2024 period, and perceived training needs. Face-to-face interviews were used for data collection. Data were entered and analyzed using SPSS software, with descriptive statistics including means and proportions. Results and Conclusions: More than 85% of respondents reported participating in at least one form of continuing medical education (CME) during the study period, with the most common formats being professional training workshops and academic conferences. However, only 64.2% met the required threshold of 48 training hours over a two-year period. Physicians exhibited higher levels of participation and greater demand than nurses, especially in academic activities such as research and teaching. Overall, the demand for CME was substantial (over 90%), though a notable gap remained between expressed needs and actual participation. The findings underscore the need to diversify CME formats, introduce more flexible scheduling, and implement supportive policies tailored to professional roles, thereby enhancing the effectiveness and accessibility of continuing education at the hospital.